An evaluation of a group CBT programme for children with a diagnosis of autism spectrum disorder in a school age disability service. Issue 1 (2nd January 2019) - Higgins, Edel; Slattery, Carol; Perry, John L.; O'Shea, John
ABSTRACT: Research has shown that rates of clinical anxiety levels are higher among young people with an ASD than their typically developing peers. This study conducted an exploratory investigation into the impact of a specifically tailored CBT group programme on anxiety levels in young people with ASD. The 12 week CBT programme was delivered to 12 children with a diagnosis of ASD in a children's disability team in Ireland. An embedded mixed methods design was utilised and inferences were drawn by collecting and analysing quantitative and qualitative data separately. Findings indicate CBT can be delivered successfully to a group of children with ASD. As is the nature of an embedded design, quantitative findings are reported as supportive evidence for the qualitative findings of this study. The positive preliminary findings suggest a rigorous, large scale evaluation is needed to determine the overall effectiveness of the programme with this population.